Metro infrastructure planning in Amsterdam: how are social issues managed in the absence of environmental and social impact assessment?. Issue 4 (3rd July 2020) - Mottee, Lara K.; Arts, Jos; Vanclay, Frank; Miller, Fiona; Howitt, Richard
ABSTRACT: Amsterdam's North-South Metro Line (NZL) megaproject has had a long eventful history. From the initial proposal in the 1990s, through construction in the 2000s to 2010s, to its opening in 2018, the NZL overcame many challenges. Several geotechnical incidents in the Vijzelgracht neighbourhood in 2008 cost the City of Amsterdam and the Dutch government millions of Euros. These incidents required complex recovery management actions, and there was a complete re-evaluation of the project, resulting in extensive reformulation of the project's communications and impact management strategies, and in more-transparent public participation. Despite NZL's significance, it never underwent any formal Environmental and Social Impact Assessment (ESIA), thus it provides an interesting case to consider how social impacts are addressed when there is no formal ESIA. Drawing on document review, semi-structured interviews, and a focus group, we considered the experiences of key decision-makers and project team members to learn how social impacts were assessed and managed over time in the absence of ESIA. We conclude that, when combined with appropriate urban governance frameworks, applying ESIA in urban and transport planning would improve the assessment and management of the social impacts of future megaproject infrastructure developments.